Pyrrolidine nucleoside bisphosphonates as antituberculosis agents targeting hypoxanthine-guanine phosphoribosyltransferase - Eng, Wai Soon; Rejman, Dominik; Pohl, Radek; West, Nicholas P; Woods, Kyra; Naesens, Lieve M J; Keough, Dianne T; Guddat, Luke W (European journal of medicinal chemistry, 2018)
Therapeutic treatment of tuberculosis (TB) is becoming increasingly problematic due to the emergence of drug resistant Mycobacterium tuberculosis (Mt). Thus, new targets for anti-TB drug discovery need to be identified to combat and eradicate this disease. One such target is hypoxanthine-guanine phosphoribosyltransferase (HGPRT) which synthesises the 6-oxopurine nucleoside monophosphates essential for DNA/RNA production. [3R,4R]-4-Hypoxanthin-9-yl-3-((S)-2-hydroxy-2-phosphonoethyl)oxy-1-N-(phosphonopropionyl)pyrrolidine and [3R,4R]-4-guanin-9-yl-3-((S)-2-hydroxy-2-phosphonoethyl)oxy-1-N-(phosphonopropionyl)pyrrolidine (compound 6) are the most potent inhibitors of MtHGPRT yet discovered having Ki values of 60 nM. The crystal structure of the MtHGPRT.6 complex was obtained and compared with that of human HGPRT in complex with the same inhibitor. These structures provide explanations for the 60-fold difference in the inhibition constants between these two enzymes and a foundation for the design of next generation inhibitors. In addition, crystal structures of MtHGPRT in complex with two pyrrolidine nucleoside phosphosphonate inhibitors plus pyrophosphate provide insights into the final stage of the catalytic reaction. As the first step in ascertaining if such compounds have the potential to be developed as anti-TB therapeutics, the tetra-(ethyl L-phenylalanine) tetraamide prodrug of 6 was tested in cell based assays. This compound arrested the growth of virulent Mt not only in its replicating phase (IC50 of 14 μΜ) but also in its latent phase (IC50 of 29 μΜ). Furthermore, it arrested the growth of Mt in infected macrophages (MIC50 of 85 μΜ) and has a low cytotoxicity in mammalian cells (CC50 of 132 ± 20 μM). These inhibitors are therefore viewed as forerunners of new anti-TB chemotherapeutics.
Keywords: Pyrrolidine nucleoside bisphosphonates; Diphosphonates; THP-1 Cells; Nucleosides; Pyrrolidines; Structure-Activity Relationship; THP-1 buňky; Antitubercular Agents; molekulární struktura; Molecular Structure; nukleosidy; Microbial Sensitivity Tests; vztah mezi dávkou a účinkem léčiva; inhibitory enzymů; Enzyme Inhibitors; pyrrolidiny; antituberkulotika; Pyrrolidine nucleoside phosphonates; vztahy mezi strukturou a aktivitou; kultivované buňky; Hypoxanthine-guanine phosphoribosyltransferase; lidé; Humans; mikrobiální testy citlivosti; bisfosfonáty; Cells, Cultured; X-ray crystal structures; Hypoxanthine Phosphoribosyltransferase; Phosphoramidate prodrugs; Therapeutic drug leads; Dose-Response Relationship, Drug; hypoxanthinfosforibosyltransferasa; Mycobacterium tuberculosis